Resident’s support towards local cultural festival in Kota Bharu, Kelantan - Asmahany, Ramely (2021)
Local cultural festivals are unique in nature and represented an integral part of cultural identity and its symbolic meaning. Residents’ support for other types of tourist attractions have been extensively researched yet studies on residents’ support towards local cultural festivals, as tourist attractions is still particularly limited. In addition, a considerable amount of attention has also been given to the dimension of residents’ support for tourism attraction development. However, there is a need to clarify its constructs and determinants that warrants a more structured theoretical framework and empirical method that may extend the work developed in past studies. Furthermore, the instrument and measurement item to assess the factors affecting residents’ support towards the tourist attraction development are urgently required. Measures have been vulnerable by lack of clarity in the theoretical framework and empirical method for the residents’ support construct. Therefore, this study sets its aim to develop the measurement constructs and items for residents’ support and determined the relationships between this variable with others. The social exchange theory, the theory of power and the concept of trust guided this study and a 52-items instrument were developed to aid a better understanding of the factors affecting residents’ support towards the development of local cultural festivals as tourist attractions in Kota Bharu, Kelantan. Testing of hypothesized relationships between residents’ factors and the decision to support revealed that perceived benefit, perceived cost, political trust, and religiosity, have significantly influenced the residents’ support toward local cultural festivals as tourist attractions. This study contributed to rigorous empirical research to strengthen the understanding of residents’ support towards tourist attraction development. Findings from this study narrow the gap in the knowledge of residents’ support towards the development of local cultural festivals as a tourism attraction. Significantly, it served as a starting point for more directed research in this area of study.